Method for preparing oversized ultrathin kaolinite nanosheet by pressurizing, intercalating and stripping
Through the coordinated coupling of chemical intercalation, macromolecular composite dispersion, and medium and low pressure gas intercalation processes, the problems of sheet crushing and low efficiency in the kaolin flake stripping process were solved, and ultra-large-sized ultra-thin kaolin stone nanosheets were prepared, which significantly improved the ceramics and the properties of hemostatic materials.
Patent Information
- Application Number
- CN202411235701.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-04
AI Technical Summary
The existing kaolin stripping process is difficult to meet the processing technology requirements of ultra-large ultra-thin kaolin nanosheets with sheet size greater than 2μm, sheet thickness less than 20nm, and diameter-thickness ratio greater than 100:1. There are sheet crushing and sheet stripping efficiency. question.
The chemical intercalation, macromolecular composite dispersion, and medium and low pressure gas intercalation technology are used to prepare ultra-large-sized ultra-thin kaolin stone nanometers with good universality through high shear flow field and ultrasonic treatment, combined with freeze-drying technology. piece.
The preparation of nanosheets with large sheet size, thin thickness and high diameter and thickness ratio of kaolin has been achieved, which significantly improves the compressive strength and hemostatic performance of ceramic microspheres, which is far higher than the effects of traditional mechanical sheet stripping and chemical intercalation methods.
Smart Images

Figure CN119191310A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of non-metallic mineral processing, and in particular relates to a method for preparing ultra-large-sized ultra-thin kaolinite nanosheets by pressurized intercalation and peeling. Background Art
[0002] Kaolin is a common natural mineral with broad application prospects in the fields of ceramics, coatings, rubber, concrete, refractory materials, etc., especially in high-temperature resistant ceramic parts in high-end fields such as aerospace and energy. Kaolin with a special lamellar structure can significantly improve the surface and interface application performance of ceramics. In recent years, the development of military hemostatic materials and aerospace molecular sieves has put forward higher requirements on the lamellar size of ultra-thin kaolin. Studies have shown that larger-sized ultra-thin kaolin can improve the hemostatic speed of military hemostatic materials and enhance the strength of aerospace molecular sieve microspheres.
[0003] Kaolinite, as the main component of kaolin, is a 1:1 type layered silicate mineral composed of silicon-oxygen tetrahedral layers and aluminum-oxygen octahedral layers. The layers are linked by hydrogen bonds and generally exist in book-like stacks. The average size of its natural flakes is about 4-10μm and the thickness is about 50-200nm. The intercalation and exfoliation of these stacked kaolinites can significantly improve the diameter-to-thickness ratio and specific surface area of kaolin, thereby obtaining natural ore raw materials with excellent flake interface composite ability.
[0004] However, the research on efficient kaolin flaking has always been a difficult point in the kaolin industry. Currently, the main processes include physical flaking, chemical intercalation flaking, and the combination of physical and chemical methods.
[0005] Physical flaking processes such as ball milling and sand milling, as flaking methods commonly used in my country's kaolin industry for decades, have disadvantages such as large flaking damage, low diameter-to-thickness ratio, large flaking thickness, and low specific surface area. Taking the kaolin production of several leading kaolin companies in my country as an example, the sand mill flaking process currently used, as the flaking time increases, although the specific surface area of kaolin will increase and the particle size will decrease, the kaolin flaking particles will be significantly damaged under high-speed flaking, and iron-containing impurities will gradually be exposed. There are problems such as low diameter-to-thickness ratio, insufficient flaking thickness, and gradual blackening of kaolin powder, which will affect the whiteness, purity, and mechanical properties such as compressive strength and flexural strength of the ceramic. Guo A-ming et al. (China Nonmetallic Minerals. 2013, 5, 36-38) used a GJ5×2 double-slot high-intensity mixing mill (375rpm) and a GXMB500 high-efficiency mill with large-size grinding media (1.5-2.5mm zirconia ceramic balls) to grind Longyan kaolin at low speed (480rpm) for 2h to obtain 60-grade and 70-grade super kaolin products. The -2μm content of the raw ore could only be increased from 25.1% to more than 60 and 70%, and its natural whiteness was seriously reduced. Zhang et al. (Applied Clay Science. 2017, 147, 117–122) used a small-size grinding media (1.2mm zirconia ceramic balls) to grind at high speed (2000rpm) for 2h and found that the kaolin lamellar structure was severely broken and the diameter-to-thickness ratio did not decrease significantly. In addition, in the 1990s, domestic and foreign countries had developed ultrafine flaking homogenizers for ultrafine processing of kaolin. For example, Pan Yecai et al. (Non-metallic Minerals, 1997, 03, 48-50) used a high-pressure homogenizer (working pressure 20-70MPa) to spray kaolin slurry at high speed on a special target and achieve ultrafine crushing under the intense collision between particles and targets and between particles. However, this process was eliminated due to poor flaking effect and easy equipment wear caused by particle collision. In general, low-speed grinding and stripping will have problems such as low grinding efficiency and thick kaolin product flakes, while high-speed mechanical ball milling with small-size media will have problems such as severe flake crushing after grinding and low diameter-to-thickness ratio.
[0006] The chemical intercalation and exfoliation method is to insert small molecule intercalation agents such as dimethyl sulfoxide, potassium acetate and urea or macromolecular intercalation agents into the interlayers of kaolin, and then realize exfoliation by controlling the removal process of the intercalation agent. The Chinese patent with patent number CN100404626C uses kaolin and potassium acetate to mix, grind and intercalate, and then wash to obtain ultrafine kaolin, but the obtained kaolin has the disadvantage that the thickness of the flakes is not thin enough. The Chinese patent with publication number CN101746768B uses chemical intercalation, grinding and spray drying to obtain a hexagonal exfoliated kaolin crystal with a diameter-to-thickness ratio of 10~30:1 and a flake thickness of less than 200nm. Liu et al. (Applied Clay Science. 2016, 124-125, 175-182) used DMSO intercalated kaolin as a precursor and significantly increased its specific surface area from 9.98 m2 of the original ore through methanol grafting and long-chain macromolecular replacement. 2 / g increased to 50.9m 2 / g, however, the product obtained by this method is a tubular kaolin nanoscroll. In general, the chemical intercalation and exfoliation process alone has problems such as thick sheets or curled nanotubes.
[0007] In terms of mechanical force-assisted physical and chemical methods combined with intercalation and flaking processes, Zhang et al. (Applied Clay Science. 2017, 147, 117–122) obtained a kaolin with a diameter-to-thickness ratio of up to 14.2 and a large lamella thickness by potassium acetate intercalation and high-speed grinding. The Chinese patent with publication number CN1994961A obtained an average kaolin lamella thickness of 30.27-79.3nm by potassium acetate intercalation and ultrasonic stripping. Li Xiaoxu et al. (Applied Chemical Industry. 2012, 41, 2103-2105) used a mixed-stationary intercalation and ultrasonic stripping method to obtain a kaolin lamella thickness of 15.22nm. The Chinese patent with publication number CN1398925A prepared an ultrafine kaolin by multiple chemical intercalation and mechanical grinding and flaking, and the content of nano-scale kaolin with a size below 100nm was 20%. Fu et al. (Applied Surface Science, 2023, 635, 157778, patent CN115784249B) used intercalation, low-speed grinding, high shear dispersion, and freeze-drying to obtain ultra-thin kaolin nanosheets with large size (1.3μm), high diameter-to-thickness ratio (130:1), and low sheet thickness (<10nm).
[0008] In general, the existing mechanical force-assisted intercalation and flaking processes such as ball milling, ultrasound, and high shear dispersion still have problems such as causing kaolin flake breakage and low flaking efficiency. The average size of individual kaolin grains after flaking is generally much smaller than 2μm, which cannot meet the demand for larger ultra-thin kaolin for high-end new materials such as military hemostatic materials and molecular sieve microspheres.
[0009] In summary, in the current kaolin flaking process, the processing technology of ultra-large-sized ultra-thin kaolin nanosheets that simultaneously meet the requirements of flake size greater than 2μm, flake thickness less than 20nm, and diameter-to-thickness ratio greater than 100:1 is still the bottleneck of the current high-end kaolin raw materials. Summary of the invention
[0010] The purpose of the present invention is to provide a method for preparing ultra-large-sized and ultra-thin kaolinite nanosheets by pressurized intercalation and exfoliation in response to the above-mentioned deficiencies in the prior art. Through the synergistic coupling of chemical intercalation, macromolecular composite dispersion, and medium and low pressure gas intercalation processes, a kaolin nanosheet with ultra-large sheet size, thin sheet thickness, and high aspect ratio is finally obtained with good universality.
[0011] To achieve the above object, the present invention adopts the following technical solution: The first object of the present invention is to provide a method for preparing ultra-large-sized ultra-thin kaolinite nanosheets by pressurized intercalation and exfoliation, comprising the following steps: S1, ball-milling and sieving the kaolin ore to obtain the impurity-free kaolin for later use; S2, mixing the impurity-removed kaolin, intercalation agent and water, stirring at a certain temperature for a certain time, and obtaining a kaolin intercalation composite after centrifugation; S3, preparing kaolin composite slurry; Add hydrochloric acid solution to the container, heat to a certain temperature, add a certain amount of cellulose and dispersant, use a high shear flow field dispersion device to stir for a certain period of time to obtain a macromolecular dispersion solution, add the kaolin intercalation complex described in step S2 to the macromolecular dispersion solution, stir for a certain period of time, and obtain a dispersed kaolin composite slurry; S4, pressure intercalation and stripping; Add the kaolin composite slurry described in step S3 into a high-pressure container, close the container, add medium- and low-pressure carbon dioxide gas, and perform high-shear stirring or ultrasonic treatment under pressure conditions for a period of time, then quickly release the pressure, and quickly spray the kaolin composite slurry from the Laval nozzle of the high-pressure valve into the flexible container to obtain a stripped kaolin slurry; S5. Dilute the flaked kaolin slurry in step S4 with water, and after settling for a period of time, take the upper layer of slurry, centrifuge it, wash it with water for multiple times, add deionized water to mix well, and then quickly freeze it, and then freeze-dry it for a certain period of time to obtain large-sized ultra-thin kaolin nanosheet powder.
[0012] Furthermore, in step S1, the kaolin ore is flaky kaolin, and the origin is selected from Beihai, Maoming or Inner Mongolia; the mesh number used for sieving is 200-400 mesh.
[0013] Furthermore, in step S2, the mass ratio of the kaolin after impurities removal to water is 1:1-10, the mass ratio of the kaolin after impurities removal to the intercalation agent is 1:0.05-0.4, the stirring temperature is 25-120°C, and the stirring time is 1-72h.
[0014] Furthermore, the intercalation agent is any one of dimethyl sulfoxide, potassium acetate and urea.
[0015] Furthermore, in step S3, the concentration of the hydrochloric acid solution is 0.1~6M, the temperature is 0~150°C, and the stirring time is 1~30min; the mass ratio of kaolin intercalation composite, cellulose, and dispersant is 1: (0.01~0.2): (0.001~0.01), the stirring temperature is 0~150°C, the stirring time is 1~30min, the linear velocity of the flow field of the high shear flow field dispersion device is greater than 30m / s, and the kaolin slurry concentration in the solution is 0.1~20wt%.
[0016] Furthermore, in step S4, the pressure of the medium and low pressure carbon dioxide gas is 0.2~10MPa; the linear velocity of the flow field of the high shear stirring device is greater than 30m / s, and the stirring time is 0.1~1h; the power density of the ultrasonic treatment device is 0.01~0.1kw / L solution, and the stirring time is 0.1~15min; the slurry outflow rate of the Laval nozzle of the high pressure valve is 20~1000m / s; the Rockwell hardness HRR of the flexible container is less than 80.
[0017] Furthermore, in step S5, the mass ratio of the flaked kaolin slurry to water is 1:50-200, the sedimentation time is 1-12 hours, and the number of washing times is 1-4 times.
[0018] Furthermore, in step S5, the centrifugal speed is 3000-10000 rpm, the rapid freezing time is 1-30 min, and the freezing temperature is -50--20°C.
[0019] The second object of the present invention is to provide an ultra-large-sized ultra-thin kaolin nanosheet prepared according to the above-mentioned preparation method, wherein the average sheet size of the ultra-thin kaolin nanosheet is 3-6 μm, the average sheet thickness is 8-15 nm, and the aspect ratio is 200-400.
[0020] The third purpose of the present invention is to use the ultra-large-sized ultra-thin kaolin nanosheets prepared by the above-mentioned preparation method or the above-mentioned large-sized ultra-thin kaolin nanosheets in hemostatic materials and aerospace molecular sieves. Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects: (1) Conventional sand mill peeling, ultrasonic peeling and other processes, as the peeling time increases, the kaolin lamella particles will be significantly damaged, there are problems such as severe kaolin lamella damage, low diameter-to-thickness ratio, or kaolin powder gradually turning black. However, this method weakens the interlayer force of kaolin by using an intercalating agent, and then uses a macromolecular composite dispersion process to preliminarily pre-disperse and compound the kaolin lamellae in the kaolin slurry, and then greatly reduces the damage of the kaolin lamellae structure while pre-dissociating the stacking structure, and then achieves gas intercalation and peeling between kaolin lamellae under the intercalation effect of medium and low pressure CO2, and further achieves effective separation of kaolin lamellae by rapid pressure relief, and finally performs low-temperature shaping of the nano-lamellar structure through a freeze-drying process. The synergistic coupling of the above processes can obtain ultra-large-sized ultra-thin kaolin.
[0021] (2) The present invention has a significant kaolin exfoliation effect. According to the intercalation exfoliation process steps of the present invention, ultra-large-sized ultra-thin kaolin nanosheets with an average flake size greater than 3 μm and a thickness of about 10 nm can be obtained. The relevant indicators are much higher than those of other current methods using mechanical exfoliation and chemical intercalation exfoliation. The above results were confirmed by macroscopic (X-ray diffraction XRD pattern) and microscopic (scanning electron microscope SEM pattern) characterization tests. The mechanical properties of ceramic microspheres prepared using the present invention, such as compressive strength, are significantly improved.
[0022] (3) The ultra-thin kaolin obtained by the present invention has a flake size greater than 3-6 μm, which exceeds the size of platelets (2-4 μm). This can promote platelet aggregation and significantly shorten the hemostasis time, and is expected to break through the bottleneck of kaolin powder hemostasis performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A process flow chart of preparing ultra-large-sized ultra-thin kaolin nanosheets provided in an embodiment of the present invention; Figure 2 XRD diagram of the final product provided in Examples 1 and 2 of the present invention and Comparative Example 1; Figure 3 This is the SEM image of the kaolin nanosheets of the sample in Example 1; Figure 4 This is the element distribution mapping diagram of the sample in Example 1. DETAILED DESCRIPTION
[0024] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.
[0025] In order to solve the technical problems of low diameter-to-thickness ratio, insufficient thickness and excessive grinding causing blackening of powder and severe breakage of flakes in the existing kaolin flaking process, the present invention provides a method for preparing ultra-thin kaolin nanosheets, which is achieved by synergistic coupling of chemical intercalation, low-speed ball milling of large-size media and high-shear flow field dispersion process, and finally obtains a kaolin ultra-thin nano-processing method with good universality, large flake size, thin flake thickness, high diameter-to-thickness ratio and high specific surface area.
[0026] The principle of the preparation method of the present invention is as follows: the original idea of the present invention comes from the phenomenon that the medium-low pressure carbon dioxide gas can enter the interlayer of intercalated kaolin and promote the separation of kaolin flakes under certain conditions, which was first discovered by the inventor in an in-situ XRD test experiment. Based on the above discovery, the present invention promotes the synergistic effect of the interface of the intercalating agent, dispersant and kaolin under the movement of the medium-low pressure carbon dioxide gas between the kaolin layers, so that the kaolin flakes can be dissociated while avoiding the destruction of the large-size flake structure, and then the synergistic coupling effect of the rapid dispersion in the high shear flow field and the freeze-setting drying process is achieved to achieve efficient exfoliation and stabilization of the kaolin flake structure.
[0027] It should be noted that the medium- and low-pressure carbon dioxide gas dispersion stripping utilizes the carbon dioxide gas molecules dissolved in the slurry to enter the interlayers of the intercalated kaolin, and through rapid pressure relief, the kaolin lamellar structure is peeled off; the rapid spraying of the Laval nozzle can further promote the dispersion of kaolin nanosheets in the gas-liquid miscible body; the flexible container can prevent the kaolin nanosheets from breaking during the collision with the container.
[0028] The technical solution of the present application is exemplarily described below.
[0029] The present invention provides a method for preparing large-sized ultra-thin kaolin nanosheets. The large-sized ultra-thin kaolin nanosheets are specifically kaolin nanosheet powders with well-preserved kaolin flake morphology, ultra-large flake size (3-6 μm), high diameter-to-thickness ratio (200-400), and low flake thickness (8-15 nm). The process flow chart is as follows: Figure 1As shown, the following steps are included: Step 1: Kaolin removal The kaolin ore is ball-milled and sieved to obtain the kaolin (kaolin concentrate) after impurities are removed; Step 2: Preparation of Kaolin Intercalation Composite Slurry Weighing the impurity-removed kaolin (kaolin concentrate), intercalation agent and water into a container, mixing, stirring at a certain temperature for a certain time, and obtaining a kaolin intercalation composite after centrifugation; Step 3: Macromolecular composite dispersion Add hydrochloric acid solution into the container and heat it to a certain temperature, add a certain amount of cellulose and dispersant, use a high shear flow field dispersion device to stir for a certain period of time to obtain a macromolecular dispersed solution, add the above kaolin intercalation complex into the solution, continue to stir for a certain period of time, and obtain a dispersed kaolin composite slurry.
[0030] Step 4: Medium and low pressure gas intercalation and stripping The kaolin composite slurry is added into a high-pressure container, the container is closed, medium- and low-pressure carbon dioxide gas is added, and high-shear stirring or ultrasonic treatment is performed under pressure conditions for a period of time, and then the pressure is quickly released, and the slurry is quickly ejected from the Laval nozzle of the high-pressure valve into the flexible container to obtain the flaked kaolin slurry.
[0031] Step 5: Sedimentation, centrifugation, washing, freeze drying The exfoliated kaolin slurry is subjected to sedimentation classification, centrifugation, washing and freeze drying to obtain large-sized ultra-thin kaolin nano-sheet crystals.
[0032] Preferably, in step 1, the kaolin ore is produced from any one of Beihai, Maoming and Inner Mongolia; and the mesh number used for sieving is 200-400 mesh.
[0033] Preferably, in step 2, the mass ratio of the kaolin after impurities removal to water is 1:1-10, the mass ratio of the kaolin after impurities removal to the intercalation agent is 1:0.05-0.4, the stirring temperature is 25-120° C., and the stirring time is 1-72 h.
[0034] Preferably, in step 3, the concentration of the hydrochloric acid solution is 0.1~6M, the temperature is 0~150°C, and the stirring time is 1~30min; the mass ratio of kaolin intercalant, cellulose, and dispersant is 1:0.01-0.2:0.001-0.01, the stirring temperature is 0~150°C, the stirring time is 1~30min, and the kaolin slurry concentration in the solution is 0.1~20wt%; the high shear flow field dispersion device, the linear velocity of the flow field>30m / s.
[0035] Preferably, in step 4, the pressure of the medium- and low-pressure carbon dioxide gas is 0.2-10 MPa; the linear velocity of the flow field of the high-shear stirring device is >30 m / s, and the stirring time is 0.1-1 h; the power density of the ultrasonic treatment device is 0.01-0.1 kw / L solution, and the stirring time is 0.1-15 min; the slurry outflow velocity of the Laval nozzle of the high-pressure valve is 20-1000 m / s; and the Rockwell hardness HRR of the flexible container is <80.
[0036] Preferably, in step 5, the slurry concentration of the diluted peeled kaolin slurry is 0.1~10wt%, the sedimentation time is 1~12h, the number of washing times is 1~4 times, the quick freezing time is 1~30min, the freezing temperature is -50~-20℃; the centrifugal speed is 3000~10000rpm.
[0037] The following is an exemplary description of a method for preparing a large-sized ultra-thin kaolin nanosheet provided in the present application in combination with specific embodiments and comparative examples.
[0038] Example 1 This embodiment provides a method for preparing ultra-large-sized ultra-thin kaolinite nanosheets by pressurized intercalation and exfoliation, and the specific steps are as follows: Step 1: Kaolin removal The Beihai kaolin ore was ball-milled into powder and passed through a 200-mesh sieve to obtain the impurity-free kaolin.
[0039] Step 2: Preparation of Kaolin Intercalation Composite Slurry 2 kg of impurity-free kaolin and 10 L of 10% DMSO solution were weighed into a container, stirred and mixed, stirred at 60° C. for 12 h, and the slurry was centrifuged to obtain a kaolin intercalation composite slurry.
[0040] Step 3: Macromolecular composite dispersion Add 40L of 0.5M hydrochloric acid solution to the container and heat to 80°C, add 50g of cellulose and 5g of sodium hexametaphosphate dispersant, and stir for 15min using a high shear flow field dispersion device to obtain a macromolecular dispersed solution. Take 1kg of kaolin intercalation complex and add it to the solution, and continue stirring for 5min.
[0041] Step 4: Medium and low pressure gas intercalation and stripping Take dispersed kaolin slurry and add it into a high-pressure container. The container is closed, medium and low pressure carbon dioxide gas is added, and high shear stirring is carried out at a pressure of 5 MPa and a temperature of 40°C for 15 minutes. Then the pressure is quickly released, and the slurry is quickly ejected from the Laval nozzle of the high-pressure valve into a flexible container to obtain exfoliated kaolin slurry.
[0042] Step 5: Sedimentation, centrifugation, washing, drying The kaolin slurry after stripping was diluted to a concentration of 0.5wt%. After settling for 3 hours, the upper half of the slurry was centrifuged at 8000rpm and washed twice with water. After washing, it was quickly frozen at -20°C for 5 minutes and then freeze-dried to obtain Beihai kaolin nanosheet powder.
[0043] Example 2 Step 1: Kaolin removal The Beihai kaolin ore was ball-milled into powder and passed through a 200-mesh sieve to obtain the impurity-free kaolin.
[0044] Step 2: Preparation of Kaolin Intercalation Composite Slurry 2 kg of impurity-free kaolin and 10 L of 10% DMSO solution were weighed into a container, stirred and mixed, stirred at 60° C. for 12 h, and the slurry was centrifuged to obtain a kaolin intercalation composite slurry.
[0045] Step 3: Macromolecular composite dispersion Add 40L of 0.1M hydrochloric acid solution to the container and heat to 60°C, add 50g of cellulose and 5g of sodium hexametaphosphate dispersant, and stir for 15min using a high shear flow field dispersion device to obtain a macromolecular dispersed solution. Take 1kg of kaolin intercalation complex and add it to the solution, and continue stirring for 5min.
[0046] Step 4: Medium and low pressure gas intercalation and stripping The dispersed kaolin slurry is added into a high-pressure container, the container is closed, medium- and low-pressure carbon dioxide gas is added, and ultrasonic treatment is performed at a pressure of 10 MPa and a temperature of 40°C for 15 minutes, and then the pressure is quickly released, and the slurry is quickly ejected from the Laval nozzle of the high-pressure valve into a flexible container to obtain a stripped kaolin slurry.
[0047] Step 5: Sedimentation, centrifugation, washing, drying The kaolin slurry after stripping was diluted to a concentration of 0.5wt%. After settling for 6 hours, the upper half of the slurry was centrifuged at 8000rpm and washed twice with water. After washing, it was quickly frozen at -20°C for 5 minutes and then freeze-dried to obtain Beihai kaolin nanosheet powder.
[0048] Comparative Example 1 Beihai kaolin ore.
[0049] Comparative Example 2 Step 1: Kaolin removal The Beihai kaolin ore was ball-milled into powder and passed through a 200-mesh sieve to obtain the impurity-free kaolin.
[0050] Step 2: Grinding Weigh different masses of medium balls with a particle size of 0.6-0.8 mm (small size) and kaolin after impurities removal, add them into a sand mill and grind them at high speed (speed 2000r) for 3 hours to obtain ultrafine nano-kaolin.
[0051] Comparative Example 3 Reference (Applied Clay Science. 2017, 147, 117–122) Step 1: Kaolin removal The Zhangjiakou kaolin ore was ball-milled into powder and passed through a 200-mesh sieve.
[0052] Step 2: Intercalation 100 g of kaolin ore was mixed with 200 g of a saturated aqueous solution of potassium acetate, heated to 60° C. and stirred for reaction for three days to obtain an intercalation composite.
[0053] Step 3: Grinding After the intercalation is completed, the intercalated kaolin is ground using a GF-1100 multifunctional experimental disperser (Shenzhen Shuangye Machinery Co., Ltd.). 300g of intercalated kaolin slurry is placed in a 2L grinding bucket, and 300g of zirconium balls with a particle size of 1.2mm are added. The slurry is ground at 2000rpm at room temperature for 2h, and then the kaolin slurry is separated from the zirconium balls using a sieve. The resulting suspension is washed by repeated centrifugation until potassium acetate is completely deintercalated. Deionized water and sodium polyacrylate dispersant are added to the ground kaolin, and after redispersion and sedimentation for 3h, the upper suspension is taken and precipitated to obtain the ground kaolin.
[0054] Comparative Example 4 (1) Preparation of kaolin intercalation composites Weigh kaolin and potassium acetate in a mass ratio of 1:1, add them into a mortar, mix and grind them evenly with deionized water, transfer them into a polytetrafluoroethylene tank, seal them, and let them stand at a certain temperature for 24 hours. Take them out, wash the potassium acetate remaining on the surface of the kaolin with anhydrous ethanol, centrifuge them, and dry them at 70°C for 24 hours to obtain a kaolin-potassium acetate intercalation complex.
[0055] (2) Ultrasonic peeling Take 1 g of kaolin-potassium acetate intercalation complex and add it into 100 mL of distilled water, and ultrasonically treat or stir for 10 min.
[0056] (3) Centrifugation, washing, and oven drying The kaolin slurry after peeling was centrifuged and washed twice with anhydrous ethanol, and dried at 70°C for 24 hours to obtain the sample.
[0057] Comparative Example 5 This comparative example refers to patent CN201010183343.8.
[0058] Step 1: Kaolin removal The coal-bearing kaolin is mechanically crushed to a particle size of less than 43 microns.
[0059] Step 2: Preparation of kaolin / DMSO intercalation complex Distilled water and dimethyl sulfoxide (DMSO) were prepared into a mixed solution in a volume ratio of 1:15, and then kaolin and DMSO solution were mixed in a mass ratio of 1:10, and stirred continuously at 50°C for 4 hours, and then filtered. The obtained precipitate was washed with anhydrous ethanol, filtered, and dried to obtain a kaolin / dimethyl sulfoxide intercalation complex.
[0060] Step 3: Preparation of kaolin / urea intercalation composite The kaolin / dimethyl sulfoxide intercalation complex was mixed with a urea solution having a concentration of 11 mol / L at a mass ratio of 1:12, reacted at 20° C. under stirring conditions for 2 h, filtered, washed with distilled water, filtered, and dried to obtain a kaolin / urea intercalation complex.
[0061] Step 4: Grinding The kaolin / urea intercalation composite, zirconium silicate grinding medium balls and saturated urea solution were placed in a flaking machine at a volume ratio of 1:2.5:0.8 for mechanical flaking for 4 hours, washed, centrifuged and dried for later use.
[0062] Step 5: Calcination The mechanically exfoliated kaolin / urea intercalation composite was heated at 160°C for 0.5 h.
[0063] Step 6: Ultrasound The heat-treated sample was placed in 95°C distilled water for ultrasonic treatment for 0.5h, then filtered and dried; and kaolin flake crystals were obtained by breaking them up with a high-speed mixer.
[0064] Comparative Example 6 This comparative example refers to patent CN202211633704.3.
[0065] Step 1: Kaolin removal The Beihai kaolin ore was ball-milled into powder and passed through a 200-mesh sieve to obtain the impurity-free kaolin.
[0066] Step 2: Preparation of Kaolin Intercalation Composite Slurry 6 g of kaolin after impurity removal and 60 ml of DMSO solution containing 10% water were accurately weighed into a container, stirred and mixed, and stirred at 60° C. for 12 h to obtain a kaolin intercalation composite slurry.
[0067] Step 3: Ball milling Weigh 32 g and 5 g of medium balls with a particle size of 1 mm and 2 mm, the above-mentioned kaolin intercalation slurry and a sodium hexametaphosphate dispersant with a slurry mass fraction of 5%, and add them to the grinding and flaking equipment. Ball mill for 30 minutes and rest for 5 minutes. The speed of the grinding and flaking equipment is 300 rpm. After a total grinding time of 2 hours, a DMSO / kaolin intercalation complex is obtained.
[0068] Step 4: Scattering the flakes Add the DMSO / kaolin intercalation complex slurry and distilled water that have been uniformly stirred after ball milling into a beaker, and use a high shear flow field dispersion device for flaking dispersion. The linear velocity of the flow field is >30m / s, and the stirring time is 0.1-2h to obtain flaked kaolin slurry.
[0069] Step 5: Sedimentation, centrifugation, washing, freeze drying The kaolin slurry after stripping was diluted at a ratio of 1:100. After settling for 2 hours, the supernatant was centrifuged at 8000rpm, the supernatant was poured out, and alcohol was added for washing 3 times. After washing, 10 ml of deionized water was added and shaken, and the mixture was placed in a refrigerator at -20°C to freeze into ice, and then placed in a freeze dryer for freeze drying for a certain period of time to obtain Beihai kaolin nanosheet powder.
[0070] Comparative Example 7 The difference from Example 2 is that step 3 (macromolecular composite dispersion) and step 4 (medium and low pressure gas intercalation and exfoliation) are not performed, and the other steps and parameters are the same as those in Example 2.
[0071] Result detection and analysis The final products of Examples 1, 2 and Comparative Example 1 were subjected to XRD detection. Figure 2 As shown, the intensity of the diffraction peak of the kaolinite (001) crystal plane in Example 1 and Example 2 using the technology of the present invention is greatly reduced and obviously broadened, indicating that the thickness of the lamellae of the main mineral component (kaolinite) of the Beihai kaolin is greatly reduced after flaking.
[0072] The SEM results of Example 1 are shown in Figure 3 As shown in the figure, compared with the original Beihai ore, its lamellae have been peeled off from the original orderly stacked thick lamellae structure (about 40nm) to a thin lamellae structure with complete lamellae. The size statistics of kaolinite nanosheets in the SEM image show that the average size of kaolinite nanosheets is 3-6μm, the average thickness of the lamellae is 8~11nm, and the diameter-to-thickness ratio is 200~400. In addition, the lamellae of the above ultra-large-sized ultra-thin kaolinite are partially bent, such as Figure 3 As shown in the enlarged part, the pore volume between kaolinite particles is further increased.
[0073] The specific surface area, pore volume, aspect ratio, sheet thickness and average sheet size of the final products of Examples 1-2 and Comparative Examples 1-7 are shown in Table 1 below.
[0074] Table 1 is a table showing the diameter-to-thickness ratio, sheet thickness, sheet average, specific surface area, and pore volume of each embodiment and comparative example.
[0075]
[0076] Note: (a) The diameter-to-thickness ratio of the sample is obtained by counting the size and thickness of the kaolinite flakes in the high-resolution SEM image of the sample. (b) The flake thickness of the sample is obtained by fitting the (001) peak of the XRD data and calculating it according to the Scherrer formula D001=kλ / βCosθ. The data is taken from the quantitative XRD test with a scanning speed of 1° / min.
[0077] As can be seen from Table 1, the kaolin obtained in Examples 1-2 of the present application, compared with the Beihai kaolin ore in Comparative Example 1, significantly improves the diameter-to-thickness ratio (up to 400:1) and the lamella thickness (the thinnest can be about 10 nm), while retaining the lamella size of natural kaolin (about 4 μm) to the maximum extent, and significantly improves the specific surface area and pore volume (nearly 2 to 5 times that of the original ore).
[0078] It can be seen that the indexes such as the diameter-to-thickness ratio, the sheet thickness, and the sheet size of Examples 1 to 2 of the present invention are far superior to those of the methods such as Comparative Examples 4 to 7. It can be seen from the data in the corresponding table of Example 1 and Comparative Examples 2 to 7 that the use of grinding, ultrasonic and other processes instead of the medium-low pressure gas intercalation and exfoliation process of the present application for exfoliation will lead to the destruction of the sheet structure of the product and a significant decrease in the sheet size; it can be seen from the data in the corresponding table of Example 1 and Comparative Examples 2 and 6 that the dispersion exfoliation of the present application retains the size of the kaolin sheet more intact, and can obtain an ultra-large-sized ultra-thin kaolin nanosheet with a kaolin sheet size greater than 4 μm; it can be seen from the data in the corresponding table of Example 1 and Comparative Examples 6 and 7 that the present application can achieve a significant reduction in the thickness of the kaolin sheet while preserving the large flaky structure of kaolin through the technical improvements and synergistic effects of processes such as intercalation, macromolecular composite dispersion, medium-low pressure gas intercalation and exfoliation, and graded drying, thereby obtaining an ultra-large-sized ultra-thin kaolin nanosheet powder.
[0079] The use of medium and low pressure gas intercalation is a new intercalation technology, which is completely different from the current kaolin intercalation and stripping technology at home and abroad. Its principle of using gas as an intercalation agent to promote the stripping of layered materials can be extended to the intercalation and stripping of other layered materials.
[0080] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing ultra-large-sized ultra-thin kaolinite nanosheets by pressurized intercalation and exfoliation, characterized in that: The following steps are involved: S1, ball-milling and sieving the kaolin ore to obtain the impurity-free kaolin for later use; S2, mixing the impurity-removed kaolin, intercalation agent and water, stirring at a certain temperature for a certain time, and obtaining a kaolin intercalation composite after centrifugation; S3, preparing kaolin composite slurry; Add hydrochloric acid solution to the container, heat to a certain temperature, add a certain amount of cellulose and dispersant, use a high shear flow field dispersion device to stir for a certain period of time to obtain a macromolecular dispersion solution, add the kaolin intercalation complex described in step S2 to the macromolecular dispersion solution, stir for a certain period of time, and obtain a dispersed kaolin composite slurry; S4, pressure intercalation and stripping; Add the kaolin composite slurry described in step S3 into a high-pressure container, close the container, add medium- and low-pressure carbon dioxide gas, and perform high-shear stirring or ultrasonic treatment under pressure conditions for a period of time, then quickly release the pressure, and quickly spray the kaolin composite slurry from the Laval nozzle of the high-pressure valve into the flexible container to obtain a stripped kaolin slurry; S5. Dilute the flaked kaolin slurry in step S4 with water, and after settling for a period of time, take the upper layer of slurry, centrifuge it, wash it with water for multiple times, add deionized water to mix well, and then quickly freeze it, and then freeze-dry it for a certain period of time to obtain large-sized ultra-thin kaolin nanosheet powder.
2. The method according to claim 1, characterized in that In step S1, the kaolin ore is flaky kaolin, and the origin is selected from Beihai, Maoming or Inner Mongolia; the mesh number used for sieving is 200-400 mesh.
3. The method according to claim 1, characterized in that In step S2, the mass ratio of the kaolin after impurities removal to water is 1:1-10, the mass ratio of the kaolin after impurities removal to the intercalation agent is 1:0.05-0.4, the stirring temperature is 25-120°C, and the stirring time is 1-72h.
4. The method according to claim 3, characterized in that The intercalant is any one of dimethyl sulfoxide, potassium acetate and urea.
5. The method according to claim 1, characterized in that In step S3, the concentration of the hydrochloric acid solution is 0.1~6M, the heating temperature is 0~150°C, and the stirring time is 1~30min; the mass ratio of kaolin intercalation composite, cellulose, and dispersant is 1: (0.01~0.2): (0.001~0.01), the stirring temperature is 0~150°C, the stirring time is 1~30min, the linear velocity of the flow field of the high shear flow field dispersion device is greater than 30m / s, and the kaolin slurry concentration in the solution is 0.1~20wt%.
6. The method according to claim 1, characterized in that In step S4, the pressure of the medium and low pressure carbon dioxide gas is 0.2~10MPa; the linear velocity of the flow field of the high shear stirring device is greater than 30m / s, and the stirring time is 0.1~1h; the power density of the ultrasonic treatment device is 0.01~0.1kw / L solution, and the stirring time is 0.1~15min; the slurry outflow rate of the Laval nozzle of the high pressure valve is 20~1000m / s; the Rockwell hardness HRR of the flexible container is less than 80.
7. The method according to claim 1, characterized in that In step S5, the mass ratio of the flaked kaolin slurry to water is 1:50-200, the sedimentation time is 1-12 hours, and the number of washing times is 1-4 times.
8. The method according to claim 7, characterized in that In step S5, the centrifugal speed is 3000-10000 rpm, the rapid freezing time is 1-30 min, and the freezing temperature is -50--20°C.
9. The ultra-large-sized ultra-thin kaolin nanosheet prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The large-size ultra-thin kaolin nanosheets have an average sheet size of 3-6 μm, an average sheet thickness of 8-15 nm, and an aspect ratio of 200-400.
10. Use of the ultra-large-sized ultra-thin kaolin nanosheets prepared by the preparation method according to any one of claims 1 to 8 or the large-sized ultra-thin kaolin nanosheets according to claim 9 in hemostatic materials and aerospace molecular sieves.
Citation Information
Patent Citations
Dissociation method of coal-series hard kaolinite rock lamella
CN103289447A
Preparing method of oxidized graphene and high-conductivity graphene
CN106564891A
Method for preparing nanosheet through gas molecule assisted intercalation-stripping
CN113213546A
Cellulose / montmorillonite nanometer composite material and its preparation method
CN1869114A
Mass production of nano-scaled platelets and products
US7785492B1
